The Gentrification Towards Afro-American Urban Cowboy Reflected in Ricky Staub’s Concrete Cowboy (2020) Movie - Azzahra, Annida Yasfa; X, Christina (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2025)
This study aims to analyze the gentrification that eliminates the urban cowboy community reflected in Ricky Staub's Concrete Cowboy (2020) and the impacts of gentrification on the urban cowboy community reflected in Ricky Staub's Concrete Cowboy (2020). The study employs a descriptive-qualitative approach to scrutinize Ricky Staub's Concrete Cowboy (2020) as its primary research objective. The research method's data analysis includes watching, reading, identifying, classifying, simplifying, and selecting. The research method involves displaying, explaining, and interpreting the data. The researcher analyzes the data using Gentrification Studies by Rowland Atkinson. The results of this research have shown that there is a process of elimination of the black urban cowboy community through gentrification with developers entering the Fletcher Street Stables area in Ricky Staub's Concrete Cowboy (2020). The impact of gentrification on urban cowboy communities can also be seen in Ricky Staub's Concrete Cowboy (2020), including four data on displacement and eviction, four data on community conflict and crime, four data on racial segregation, and one data on homelessness.